(untitled) (Journal of Engineering, 2015)
This research is carried out to investigate the externally post-tensioning technique for strengthening RC beams. In this research, four T-section RC beams having the same dimensions and material properties were casted and tested up to failure by applying two mid-third concentrated loads. Three of these beams are strengthened by using external tendons, while the remaining beam is kept without strengthening as a control beam. Two external strands of 12 mm diameter were fixed at each side of the web of the strengthened beams and located at depth of 200 mm from top fiber of the section (dps). So that the depth of strands to overall depth of the section ratio (dps /h=0.8). For each strengthened beams, the strands have been tensioned by using a hydraulic jack with constant stress of 600 MPa. The main parameter conducting in this research is the strengthening length ratio (Ls/L) which is equal to the length of strengthening region (Ls) divided to the length of beam (L), these ratios are 0.83, 0.67 and 0.50. The experimental results showed that this technique for strengthening is efficient for reducing cracks width and increasing first cracking, service cracking and ultimate load capacities. The percentage increasing in first crack loads were 100%, 133% and 167%, for service crack loads (0.3 mm) were 63%, 75% and 88% and for ultimate loads were 78%, 89% and 67% for strengthening length ratios 0.83, 0.67 and 0.50 respectiviely as compared with the control beam.